Sinergi Pemanfaatan Big Data dengan Sharing Data Privacy Pengguna: Efek Menawarkan Kompensasi dalam Meyakinkan Pengguna E-Wallet - Sudyasjayanti, Christina; Rahmania, Laili (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
The development of digital payment transactions through the adoption of e-wallets has a significant impact on the utilization of big data by companies and user data security systems. The purpose of this study is to ascertain how providing users with financial incentives and control over data use will enhance their willingness to divulge personal information to businesses. Additionally, assessing the variables that may affect a person's willingness to divulge personal information. 130 members of Generation Z in Surabaya who have utilized ShopeePay provided the data for this study. To evaluate the suggested hypotheses and examine the correlations between variables, the data were analyzed using SEM-PLS modeling with Smart-PLS 3 software. According to the study's findings, providing financial incentives and control over data use as compensation can make people more ready to divulge personal information. However, perceived data sensitivity does not reduce the willingness to share personal information. The mediation relationship was identified, where perceived data sensitivity did not mediate control compensation. This shows that providing compensation in the form of control compensation and monetary compensation has a major influence in motivating individual preferences for sharing user personal data.